Enhancing Graduate Competitiveness Through PDCA-Driven Curriculum Management - Faradifa Evrillia Haniyan; Deti Rosdini (Papanda Publisher, 2026)
Vocational education must respond dynamically to evolving industry demands through systematic curriculum management. The Plan-Do-Check-Act (PDCA) framework offers potential for continuous improvement, yet its application in resource-limited vocational schools remains underexplored. This qualitative case study examined PDCA implementation at SMK Mathla'ul Anwar Margahayu through in-depth interviews with school leaders (n=2), teachers (n=6), and industry partners (n=4), complemented by classroom observations and curriculum document analysis. Data were analyzed using Miles and Huberman's interactive model with triangulation ensuring trustworthiness. PDCA implementation demonstrated systematic improvements across all stages: industry-informed planning through structured stakeholder engagement, authentic implementation integrating Teaching Factory and Product-Based Learning (87.5% of lessons), reflective criteria-based evaluation with 78% of student products meeting industry standards, and evidence-based curriculum revisions. Five enabling factors emerged—visionary leadership, strategic partnerships, teacher professionalization, data-driven culture, and policy support—while four constraints were identified: infrastructure limitations, resource insufficiencies, teacher workload, and diverse industry requirements. Findings advance theoretical understanding by introducing